Enhancing Five-Axis Machining Models Using Advanced Geometric and Differential Techniques - سلوم, تمام (Latakia University Journal -Engineering Sciences Series, 2025)
This study aims to develop and analyze the direct and inverse geometric and differential models of a five-axis CNC machine. The research seeks to bridge the gap between theoretical models and practical applications, contributing to improved design and control techniques for programmed machines. The CATIA V5 software was utilized to design and assemble the machine's various components, while mathematical matrices were employed to analyze the relationships among multiple axes. Additionally, the concept of "Jerk" and its significance in enhancing machine performance were explained, with an emphasis on its role in reducing vibrations and improving the quality of machined surfaces. The results demonstrated a strong alignment between the developed models and practical applications, achieving a 15% improvement in coordinate accuracy and reducing machining time. Simulations conducted using MATLAB validated the models' effectiveness in analyzing machine performance and guiding operations. The conclusions emphasize the importance of employing direct and inverse geometric and differential models to enhance five-axis machine operations and advance applications in engineering industries. The study recommends integrating these models with artificial intelligence techniques to achieve further enhancements.